2013
DOI: 10.1186/2045-3329-3-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in Epstein-Barr virus-associated post-transplant smooth muscle tumours is related to leiomyomatous phenotype

Abstract: Epstein-Barr virus (EBV)-associated post-transplant smooth muscle tumours (PTSMT) are rare complications. In our previous molecular analysis, we have evaluated the expression of regulatory microRNA which are known to be EBV-related (miR-146a and miR-155) but found no deregulation in PTSMT. In this current analysis, we aimed to characterize the expression profiles of several hundred microRNA. Tissue samples from PTSMT and uterine leiomyomas were analysed by quantitative real-time PCR for the expression of 365 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…However, these signaling pathways do not appear to induce miR-155 expression in EBV-positive cells. EBV infection can induce miR-155 expression (Cameron et al, 2008; Imig et al, 2011; Jonigk et al, 2013; Yin et al, 2008a; Zhu et al, 2014), and EBV latent genes such as LMP1 and LMP2A have been shown to induce miR-155 expression (Du et al, 2011; Gatto et al, 2008; Rahadiani et al, 2008). Nevertheless, the level of miR-155 activation by LMP1 and LMP2A is not comparable to the level of miR-155 induction by EBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, these signaling pathways do not appear to induce miR-155 expression in EBV-positive cells. EBV infection can induce miR-155 expression (Cameron et al, 2008; Imig et al, 2011; Jonigk et al, 2013; Yin et al, 2008a; Zhu et al, 2014), and EBV latent genes such as LMP1 and LMP2A have been shown to induce miR-155 expression (Du et al, 2011; Gatto et al, 2008; Rahadiani et al, 2008). Nevertheless, the level of miR-155 activation by LMP1 and LMP2A is not comparable to the level of miR-155 induction by EBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…A surprisingly large number of different types of potentially incapacitating or lethal viruses, possessing either DNA or RNA genomes, have been shown to significantly induce miRNA-146a in the human CNS, immune, lymphatic, hepatic or circulatory systems, and these include (alphabetically-ordered): (i) Chikungunya virus (CHIKV; Togaviridae; (+)ssRNA genome; Selvamani et al, 2014 ); (ii) enterovirus 71 (EV71; Picornaviridae ; (+)ssRNA genome; Ho et al, 2014 ); (iii) Epstein-Barr virus (EBV; Herpesviridae ; dsDNA genome; Jonigk et al, 2013 ); (iv) Hantavirus (HTV; Bunyaviridae; (−)ssRNA genome; Shin et al, 2013 ); (v) hepatitis C virus (HCV; Flaviviridae ; (+)ssRNA genome; Joshi et al, 2013 ); (vi) herpes simplex virus-1 (HSV-1; Herpesviridae ; dsDNA genome; Higaki et al, 2003 ; Hill et al, 2009 ; Lukiw et al, 2010 ); (vii) Henipavirus (Hendra) virus (HeV; Paramyxoviridae ; (−)ssRNA genome; Stewart et al, 2013 ); (viii) human influenza A viruses (H1N1/H3N2; Orthomyxoviridae ; (+)ssRNA genome; Chen et al, 2012 ; Terrier et al, 2013 ); (ix) hepatitis B virus (HBV; Hepadnaviridae ; dsDNA genome; Liu et al, 2009 ); (x) human immunodeficiency virus (HIV; Retroviridae ; (+)ssRNA genome; Duskova et al, 2013 ; (xi) human T-cell leukemia (lymphotropic) virus type 1 (HTLV-1; Retroviridae ; (+)ssRNA genome; Pichler et al, 2008 ); and (xii) Japanese encephalitis virus (JEV; Flaviviridae; (+)ssRNA genome; Pareek et al, 2014 ). Note that (i) this viral-miRNA-146a-induction/association are all relatively recent discoveries with more than three quarters identified within the last 22 months; (ii) all of the most recent viral-host miRNA-nucleoplasmic signaling studies indicate the up-regulation of miRNA-146a; and (iii) viral infection involving each virus mentioned above is associated with progressive neuropathological change.…”
mentioning
confidence: 99%
“…Therefore, correct gene expression is necessary for proper palate development in both palatal epithelium and mesenchyme 22,23,24) . miRNAs microarray chip, as a kind of rapid and effi cient method to analyze the miRNAs expression profi les, has been widely used to identify the differentially expressed miRNAs in tumor 25,26) . However, there is no report about the miRNAs expression profiles in cleft palate so far.…”
Section: Discussionmentioning
confidence: 99%